Varus knee limits pain relief effects of laterally wedged insoles and ankle-foot orthoses in medial knee osteoarthritis - Bartsch, Leonie P.; Schwarze, Martin; Block, Julia; Alimusaj, Merkur; Schiltenwolf, Marcus; Jaber, Ayham; Wolf, Sebastian Immanuel (Journal of rehabilitation medicine, 2022)
Objective: To investigate the impact of varus malalignment of the knee on pain reduction achieved by an ankle-foot orthosis and a laterally wedged insole in patients with medial knee osteoarthritis.Design: Secondary analysis of a randomized, clinically prospective cross-over study.Patients: Twenty-eight participants with medial knee osteoarthritis.Methods: All participants wore a 5-mm laterally wedged insole and an ankle-foot orthosis for a period of 6 weeks each in a randomized order. Pain was reported on a numerical rating scale and was correlated with limb alignment, as defined by the mechanical axis deviation in full-leg standing radiographs.Results: Insole and orthosis use reduced pain compared with baseline (median knee pain change: insole -0.5 (-5 to +6), orthosis -1.5 (-7 to +5). A higher mechanical axis deviation (greater varus) correlated significantly with smaller pain reduction for both aids (insole p = 0.003, orthosis p < 0.001). A cut-off to predict pain response was found at a mechanical axis deviation of 14-15 mm for both aids, i.e. > 3° knee varus.Conclusion: There is a correlation between varus malalignment and pain reduction. There seems to be a mechanical axis deviation cut-off that predicts the response to treatment with the aids with good sensitivity. - LAY ABSTRACTOsteoarthritis of the knee can be treated using orthoses and insoles to unload the most damaged and painful inner (medial) part of the knee. However, patients do not benefit equally from these devices and there is not enough scientific data to predict which patients will benefit from an orthosis or insole. This study investigated whether the genu varum (degree of bow-leggedness) correlates with pain reduction when using an insole or an ankle-foot orthosis. A total of 28 patients with knee osteoarthritis received both aids, each for a period of 6 weeks, in random order. They documented knee pain before and after using the devices. Radiographs of the leg were analysed to determine the degree of genu varum. Statistical analysis showed that patients with straighter legs experienced better pain reduction with both aids than did bow-legged patients. In conclusion, ankle-foot orthoses and insoles are less effective in bow-legged patients.